2019
DOI: 10.3390/pr7080506
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nitrogen Absorption on Microstructure, Properties and Cytotoxicity Assessment of 316L Stainless Steel Alloy Reinforced with Boron and Niobium

Abstract: In the past, 316L stainless steel (SS) has been the material of choice for implant manufacturing. However, the leaching of nickel ions from the SS matrix limits its usefulness as an implant material. In this study, an efficient approach for controlling the leaching of ions and improving its properties is presented. The composition of SS was modified with the addition of boron and niobium, which was followed by sintering in nitrogen atmosphere for 8 h. The X-ray diffraction (XRD) results showed the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In vivo experiments have shown that nickel ions are released, which leads to poor resistance and adverse reactions to the biological system. For this reason, an alternative has been found to avoid this disadvantage by introducing a new type of Co-Cr alloys [78][79][80].…”
Section: Example Of Metallic Biomaterialsmentioning
confidence: 99%
“…In vivo experiments have shown that nickel ions are released, which leads to poor resistance and adverse reactions to the biological system. For this reason, an alternative has been found to avoid this disadvantage by introducing a new type of Co-Cr alloys [78][79][80].…”
Section: Example Of Metallic Biomaterialsmentioning
confidence: 99%
“…The powders mixture of predefined ratio was blended in Turbula mixer for the mixing time of 2 hours, 4 hours and 6 hours, respectively, Figure 2. Turbula mixer has been used and reported by various researchers, for the preparatory work of material formulations [17].…”
Section: Blending Of the Matrix And Reinforcement Particlesmentioning
confidence: 99%
“…The foremost commonly utilized biomaterials include Ti6Al4V, CoCrMo, and AISI 316L stainless steel [14]. Owing to its low cost, reasonable corrosion resistance, and ease of manufacturing, one of the most frequently used biomaterials in the manufacturing of implants is austenitic 316L stainless steel, the commercially available biomaterial [15,16]. The implants manufactured from this material are cheaper than titanium and cobaltbased alloys by one-tenth to one-fifth [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…To increase the performance of this material, the behaviour of simultaneous additions of boron, titanium, and niobium in stainless steel alloy can be examined. For producing a protective surface layer, consolidation factors such as compaction pressure, sintering temperature, and dwell time have not been explored in our previous studies [15,25,38,[40][41][42][43]. This research work examines the effect of material composition on the physical and mechanical properties of modified 316L stainless steel alloy.…”
Section: Introductionmentioning
confidence: 99%